ACHIEVING SUPERIOR EMPLOYEE PERFORMANCE: TALENT MANAGEMENT STRATEGIES IN ASEAN MANUFACTURING FIRMS AMID REGIONAL INTEGRATION - Irma Nurmala Dewi; Khaeruman Khaeruman; Santha Chenayah (Yayasan Education and Social Center, 2026)
The purpose of this study is to examine talent management techniques for improving employee performance in ASEAN manufacturing companies in the context of regional integration. Increasing regional competition resulting from ASEAN economic integration requires manufacturing companies to have competent, adaptable, and innovative human resources to maintain a competitive advantage. The research uses a qualitative, descriptive approach. Data were gathered through in-depth interviews, observations, and documentation of informants, including human resources managers, supervisors, and employees involved in talent development programs. The research was carried out during November-December 2025. Data analysis was conducted using NVivo to identify themes, patterns, and relationships among concepts emerging from the research data. The results show that competency development, talent retention, career management, and leadership support are the main factors that support the success of talent management strategies. The implementation of this strategy has been proven to increase work productivity, quality of work results, innovation, adaptability, and organizational commitment. The study's findings also show that talent retention is an important challenge in addressing workforce mobility in the ASEAN region. As a result, manufacturing companies must incorporate talent management into their long-term business strategy to sustainably improve employee performance and organisational competitiveness.